Interpreting real exchange rate movements in transition countries - Mark De Broeck; Torsten Sloek (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
Several transition countries have experienced strong real exchange rate appreciations.This paper tests the hypothesis that these appreciations reflect underlying productivity gains in the tradable sector.Using panel data over the period 1993 98, the results show clear evidence of productivity-driven exchange rate movements in the central and eastern European and Baltic countries.Transition countries, particularly the EU accession countries that have begun to catch up, can expect to experience further productivity-driven real exchange rate appreciations.Evidence from a large cross-section of non-transition countries indicates that catching up by one percent will be associated with a 0.4 percent real appreciation
URN:NBN:fi:bof-201408072089
Keywords: 330